Development of polymer insole in additive manufacturing for people with plantar hyperhidrosis - Camargo, Fernanda Pereira; Gomes, David Rodrigues; Alves, Lucas Repecka; Corrêa, Carlos Eduardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
The objective of this project is to develop a TPU (Thermoplastic Polyurethane) polymer insole using additive manufacturing technology, with the application of gyroid geometry. The insole is an essential component in footwear, providing comfort and support for the foot. The gyroid geometry has unique properties such as high porosity, lightness and flexibility, which makes it suitable for insole applications. Additive manufacturing allows for the precise and customized manufacturing of complex parts, which is advantageous for the production of insoles with specific geometries to meet the individual needs of each user. The project aims to explore the potential of combining these technologies to manufacture innovative and comfortable insoles, making walking easier and safer for people who suffer from plantar hyperhidrosis, a disease that characterizes excessive foot sweat. Consuming shoes that do not absorb excessive moisture limits these people to having the power of choice, therefore, a solution was proposed to adapt open shoes with a TPU insole developed through the software inventor fusion 360.